1997
DOI: 10.1038/sj.ijo.0800412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on total and free insulin-like growth factor (IGF)-1, and their relationship to IGF-binding protein (BP)-1, IGFBP-2, IGFBP-3, insulin, and growth hormone

Abstract: OBJECTIVES:We investigated the effect of obesity on the serum levels of total and free IGF-1 and their relationship to the circulating levels of insulin and IGF binding proteins (IGFBPs) in age and sex-matched groups. SUBJECTS: The study included 43 obese subjects (ideal body weight; IBW b 120%) and 45 controls (IBW`100%). All of the subjects were male. MEASUREMENT: Total IGF-1, free IGF-1, IGFBP-1, IGFBP-2, IGFBP-3, and insulin were measured in obese subjects and normal control subjects. RESULTS: No signi®can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
226
6
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(259 citation statements)
references
References 28 publications
25
226
6
2
Order By: Relevance
“…The increases in IGFBP-1 and -2 most likely caused a reduction in circulating free IGF-IFa small fraction of circulating IGF-I that is not bound by any IGF-binding protein, and that probably reflects the fraction most rapidly available to tissues for binding to cellular receptors. Other studies (Frystyk et al, 1995;Nam et al, 1997;Nyomba et al, 1997) have shown inverse correlations of plasma IGFBP-1 and -2 with plasma free IGF-I levels. Unfortunately, we had technical problems with an assay kit for measurement of free IGF-I, and thus All P-values are adjusted for treatment/intervention status, age class, insulin level, testosterone level.…”
Section: Discussionmentioning
confidence: 86%
“…The increases in IGFBP-1 and -2 most likely caused a reduction in circulating free IGF-IFa small fraction of circulating IGF-I that is not bound by any IGF-binding protein, and that probably reflects the fraction most rapidly available to tissues for binding to cellular receptors. Other studies (Frystyk et al, 1995;Nam et al, 1997;Nyomba et al, 1997) have shown inverse correlations of plasma IGFBP-1 and -2 with plasma free IGF-I levels. Unfortunately, we had technical problems with an assay kit for measurement of free IGF-I, and thus All P-values are adjusted for treatment/intervention status, age class, insulin level, testosterone level.…”
Section: Discussionmentioning
confidence: 86%
“…For example, serum insulin and IGF-I levels are elevated in obesity. 15,16 Insulin and IGF-I activate the mTOR-AKT pathway, resulting in increased proliferation and decreased apoptosis. 17 In animals, dietary-induced increased serum IGF-I and insulin levels are associated with increased PC growth.…”
Section: Discussionmentioning
confidence: 99%
“…In chronically hyperinsulinemic states, such as obesity, insulin inhibits the synthesis of IGFBP-1 and -2 and increases the free IGF-I fraction. 51,52 Insulin also increases free circulating IGF-I by downregulating the synthesis of IGF-binding proteins-1 and -2 which, together with IGFBP-3, play an important role in regulating the free fraction of IGF-I. In turn, increased free IGF-I exerts a negative feedback on pituitary GH secretion, the primary stimulus for hepatic IGF-I synthesis and causes a decrease in total IGF-I levels.…”
Section: Discussionmentioning
confidence: 99%